2019
DOI: 10.3892/ijmm.2019.4387
|View full text |Cite
|
Sign up to set email alerts
|

Dihydroartemisinin attenuates lipopolysaccharide‑induced acute lung injury in mice by suppressing NF‑κB signaling in an Nrf2‑dependent manner

Abstract: Acute lung injury (ALI) is a severe health issue with significant morbidity and mortality. Artemisinin is used for the treatment of fever and malaria in clinical practice. Dihydroartemisinin (DHA), the major active metabolite of artemisinin, plays a role in anti-organizational fibrosis and anti-neuronal cell death. However, whether DHA can attenuate ALI remains unclear. The current study thus examined the effects of DHA on ALI and primary macrophages. The results revealed that DHA attenuated lipopolysaccharide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 46 publications
6
23
0
Order By: Relevance
“…In contrast, enhanced protein levels of NRF2 have been reported to alleviate LPS-induced lung injury in mice [39,40]. In consistent with previous report [41], we found that glycine pre-administration reversed LPS-induced depletion of NRF2 and led to the increased protein level of genes implicated in cellular survival [42]. In a recent study, the authors showed that NRF2 is a repressor of NF-κB [43].…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, enhanced protein levels of NRF2 have been reported to alleviate LPS-induced lung injury in mice [39,40]. In consistent with previous report [41], we found that glycine pre-administration reversed LPS-induced depletion of NRF2 and led to the increased protein level of genes implicated in cellular survival [42]. In a recent study, the authors showed that NRF2 is a repressor of NF-κB [43].…”
Section: Discussionsupporting
confidence: 92%
“…By inhibiting expression of NF-κB signaling and enhancing heme oxygense-1 expression, the artesunate can lower the concentrations of TNF-α and IL-6 in serum and bronchoalveolar lavage fluid. Huang and colleagues discovered that dihydroartemisinin could attenuate lipopolysaccharide (LPS)-induced ALI through suppressing NF-κB signaling in a nuclear factor erythroid 2-related factor 2 (Nrf2)-dependent fashion, thereby leading to a decrease in expression of the pro-inflammatory cytokines IL-1β, TNF-α, and IL-6 ( 102 ). Hu and colleagues explored a new and efficacious approach for ALI ( 103 ).…”
Section: Potential Treatments For Cytokine Storm In Covid-19 and Theimentioning
confidence: 99%
“…To assess the relevance of Nrf2 signaling in the antiinflammatory effect of EAE in LPS-stimulated microglia, ML385, a specific Nrf2 inhibitor [50], was employed. Microglia were pretreated with or without the inhibitor (20 μM) [51], then treated with EAE followed by a further incubation with LPS. Unexpectedly, ML385 did not change the increased mRNA expression levels of Nrf2 and HO-1 induced by EAE ( Fig.…”
Section: The Anti-inflammatory Properties Of Euglena Gracilis Extractmentioning
confidence: 99%